PENDAMPINGAN LESSON STUDY BAGI GURU SMP ISLAM BAITUL MAKMUR MALANG GUNA MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA - Zuni Mitasari; Istikomayanti, Yuswa; Lathifah, Anis Samrotul; Anwar, Moh. Farid Nurul; Bulu, Marselina (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
Professional competence is one of the competencies that teachers must have. Increasing teacher professionalism can be reach through lesson study activities. In this activity, the teacher designs the lesson design together with the lesson study team. The change to the Merdeka curriculum is also a challenge for teachers, because it is still new so teachers need to collaborate with others to prepare innovative learning. The aim of community service is to provide assistance to teachers at Baitul Makmur Islamic Middle School Malang in preparing lesson designs so that they can support the implementation of the merdeka curriculum in schools. The method is carrying out FGDs, plan, do, see, and redesign learning as a form of improving further learning. Open class activities were held four times. The results of lesson study assistance activities provide benefits for increasing the professionalism of partner teachers and are expected to be in line with improving the quality of learning in the classroom so that the implementation of the merdeka curriculum can be carried out well.